Management of Maritime Human Resources in Belawan to Create a Social Creative and Innovative Society in The 4.0 Technology Era - Dirhamsyah Dirhamsyah; Dina Rispianti (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
The industrial revolution 4.0 is a condition where there are very significant changes in industrial processes carried out by humans.Digital technology's rapid development in the industrial sector, which has accelerated industrial processes, is a defining feature of this shift.The available Human Resources (HR) must, on the other hand, be able to adapt to these changes in order to keep up with global competition in the industrial world because the industrial revolution has replaced human labor. The capital available in Indonesian ports is sufficient to implement industry 4.0.Preparing human resources through secondary and higher education is the first step in developing national capability in maritime education, followed by mastery and application of marine science and technology. This capability can be realized by increasing research and development capacity and providing scholarships for maritime technical schools.The existence of Belawan Port will have a significant impact on aspects of the community's socioeconomic life as a result of the increasing visibility of its activities.The advancement of these local area exercises can't be isolated from the effect of port exercises.